1984
DOI: 10.1113/jphysiol.1984.sp015081
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin receptors and hormonal actions on water fluxes in cultured canine renal cells (MDCK line).

Abstract: SUMMARY1. An established cellular line (MDCK) derived from canine kidney showed specific binding for prostaglandin E2, both when the determination of specific binding was carried out in cells attached to a semipermeable support and when this binding was determined in suspended cells in a calcium-free medium.2. Specific binding for tritiated prostaglandin F2z was also observed, and it was inhibited by increasing concentrations of non-radioactive PGF. in a dose-related pattern. Cross-reactivity between PGE2 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Madin-Darby canine kidney cells have previously been utilized as a convenient in vitro model system for the elucidation of some aspects of the cellular action of prostaglandins on renal epithelial cells (Martinez & Reyes, 1984;Aboolian et al 1989). Hassid (1983) in particular has demonstrated that exogenous PGE2 stimulates intracellular cyclic AMP accumulation in the presence of IBMX; in the present experiments, using MDCK cells of a defined phenotype (Rugg & Simmons, 1984b), this finding has been confirmed.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Madin-Darby canine kidney cells have previously been utilized as a convenient in vitro model system for the elucidation of some aspects of the cellular action of prostaglandins on renal epithelial cells (Martinez & Reyes, 1984;Aboolian et al 1989). Hassid (1983) in particular has demonstrated that exogenous PGE2 stimulates intracellular cyclic AMP accumulation in the presence of IBMX; in the present experiments, using MDCK cells of a defined phenotype (Rugg & Simmons, 1984b), this finding has been confirmed.…”
Section: Discussionsupporting
confidence: 76%
“…In the present studies an established cultured epithelium of high electrical resistance, derived from dog kidney (MDCK), has been used to investigate a possible cellular basis for prostaglandin action upon ion transport. Prostaglandin modulation of water fluxes (Martinez & Reyes, 1984) and of intracellular Ca21 (Aboolian, Molen & Nord, 1989) have previously been reported in this cell line. The MDCK epithelium is highly differentiated (Simmons, Brown & Rugg, 1984) and expresses antigens consistent with a tubular origin in the distal/collecting tubule (Herzlinger, Easton & Ojakian, 1982;Ojakian, Romain & Herz, 1987).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…They were kept in ice-cold Ringer (4 0 C) and gassed with 02/C02 (95 %/5 %) until the beginning of the experiment. The Ringer contained (mAf): NaCl 110; KC1 5; NaHCOs Tritiated PGE2 Uptake in the Presence of Indomethacin and PAH Incubation in the presence of indomethacin in tended to inhibit the synthesis of the endogenous PGs and thus avoid the interference of these PGs with the binding of 3H-PGE2 as has been shown in cultured renal cells [Martinez and Reyes, 1984]. Both PAH and indomethacin eliminated the uptake of radiolabelled PGE2 in renal cortical slices due to tubular secretion [Meléndez and Reyes, 1982], These two fac tors interferred with an adequate estimation of the binding sites to PGs in the kidney.…”
Section: Methodsmentioning
confidence: 99%